Prevalence of dental caries among public school children in the Eastern Nepal - Bhagat, TK; Shrestha, A (Journal of Chitwan Medical College, 2014)
Aim: To assess the prevalence of dental caries among public school children of eastern Nepal using DMFT and dft index. Methods: Six hundred and sixty six school children were examined for decayed missing and filled teeth. Decayed, Missing and Filled Teeth (DMFT), decayed and filled teeth (dft) and prevalence were calculated. Results: The mean decayed and filled teeth were 1.82 whereas mean Decayed, Missing and Filled Teeth were 0.37.The prevalence of dental caries were 60.3% and 55.6% in the primary and permanent dentition respectively. Conclusion: The prevalence of dental caries was low in permanent dentition compared to primary dentition. DOI: http://dx.doi.org/10.3126/jcmc.v4i1.10845 Journal of Chitwan Medical College 2014; 4(1): 30-32